UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PECAHAN DENGAN MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING KELAS IV SDN 168060 KOTA TEBING TINGGI - Nurhaida Lubis (FIP Unimed, 2018)
ABSTRACTMathematical learning using snowball Throwing cooperative learning can improve learning outcomes of fourth grade students of SD Negeri 168060 Tebing Tinggi in 2014/2015 academic year in the ability to understand fraction material This can be seen from the increase in students' ability to understand fraction material from the pre test results in pre the cycle where the average acquisition of grade IV students is 56.87 with the percentage of completeness class 25%. In the first cycle it increased with a class average of 64.37 and a percentage of completeness of 62.5%. While in the second cycle the class average reached 81.56 with the percentage of students completing 93.7%. From the results of these tests it can be concluded that this research can be said to be successful. Keywords: Learning Outcomes, Snowball Throwing, Fractions ABSTRAK Pembelajaran matematika dengan menggunakan pembelajaran kooperatif tipe snowball Throwing dapat meningkatkan hasil belajar siswa kelas IV SD Negeri 168060 kota Tebing Tinggi Tahun Pelajaran 2014/2015 dalam kemampuan memahami materi pecahan Hal Ini dapat dilihat dari peningkatan kemampuan siswa dalam memahami materi pecahan dari hasil pre tes pada pra siklus dimana rata rata perolehan siswa siswa kelas IV adalah 56,87 dengan persentase ketuntasan kelas 25%. Pada siklus I meningkat dengan rata-rata kelas 64,37 dan persentase ketuntasan 62,5%. Sedangkan pada siklus II rata-rata kelas mencapai 81,56 dengan persentase ketuntasan siswa 93,7%. Dari hasil tes tersebut dapat diambil kesimpulan bahwa penelitian ini dapat dikatakan berhasil. Kata Kunci: Hasil Belajar, Snowball Throwing, Pecahan